Integration of Tridharma in the Islamic Digital Finance Course “Navigating the Future of Islamic Finance: Islamic Fintech Innovations and Opportunities” - Antonio, Muhammad Syafii; Syamlan, Yaser Taufik (Tamkin Jurnal Pemberdayaan Tazkia, 2025)
In this modern era marked by rapid advancements in knowledge and technology, changes are occurring across various domains of life. One response to these changes is community engagement, which aims to integrate innovations and new knowledge into everyday life. In this context, the organized community engagement has three primary objectives that are highly significant. Firstly, community engagement aims to integrate Islamic digital finance courses with community empowerment. This entails not only providing training or courses on Islamic digital finance but also imparting understanding and skills to the community in applying these concepts in their daily lives. Consequently, communities can benefit from technological advancements in the context of Islamic finance, thereby enhancing financial inclusion and economic empowerment. Secondly, community engagement aims to enhance Tazkia's image as a pioneer in Islamic digital business and finance. Through these activities, Tazkia can demonstrate its commitment to innovation and development in the field of Islamic finance. This not only helps improve the institution's reputation but also strengthens its position as a leading center in Islamic finance education and research. Thirdly, community engagement aims to market TAZKIA to the targeted market segments. By organizing relevant and informative seminars and talk shows, Tazkia can reach a wider audience and introduce its services to them. This is a crucial step in expanding the institution's reach and increasing community participation in the programs offered. In addition to these three primary objectives, community engagement also has further impacts. For instance, through outputs such as articles written by Tazkia students, this engagement can strengthen student involvement in academic activities and provide a platform for them to share their knowledge and experiences. Furthermore, by providing theoretical and practical knowledge to participants, community engagement is expected to make a tangible contribution to the development of the Islamic digital finance sector and community empowerment on a broader scale.